Exploring the Socio-Cultural Determinants of Dowry Practice: A Qualitative Study of Dir Lower, Khyber Pakhtunkhwa - Yousaf Khan,; Dr. Ahmad Ali,; Dr. Sameer Ul Khaliq Jan*, (Dialogue Social Science Review (DSSR), 2025)
Dowry is a common tradition in South Asian countries, especially in Pakistan. Dowry refers to jewelry, kitchen utensils, clothes, gifts, cash, and other items given by the bride’s family to the groom at the time of marriage. Dowry has become a serious problem in our society today. This research study aims to investigate the determinants of dowry in female marriages in District Dir Lower, Khyber Pakhtunkhwa, Pakistan. The nature of the current study was qualitative. Data were collected from 13 respondents using a snowball sampling technique through an interview guide. The collected data were analyzed using thematic analysis. The results show that dowry has deep roots in society because the family setup itself encourages the practice of paying a substantial dowry. Dowry is considered a source of honor and prestige for the bride in the eyes of her husband. Women who bring a large dowry are treated respectfully by their in-laws, while those with a small dowry are often mistreated, insulted, disliked, and sometimes even thrown out of their homes. The payment of a large dowry may influence the decision to delay marriage for girls. People's perceptions indicate that dowry is no longer just a custom or tradition in our country—it has become a trend that people follow. The study recommends that the government educate the public, as awareness can play an important role in reducing dowry practices. Religious scholars should emphasize the true teachings of Islam regarding dowry and discourage all harmful traditional practices. This will directly improve the status of Pakistani women, despite the patriarchal nature of Pakistani society. Moreover, based on the findings of the study, community elders, NGOs, social workers, and social mobilizers must play their roles in minimizing dowry demands. These efforts can help make the practice manageable or eliminate it entirely, thereby addressing this serious issue. Keywords: Socio-Cultural Determinants, Dowry Practice, Perception, Dir Lower, Khyber Pakhtunkhwa